2013
DOI: 10.1371/journal.pone.0079572
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Acidic Tail of High Mobility Group Protein B1 (HMGB1) in Protein Stability and DNA Bending

Abstract: High mobility group box (HMGB) proteins are abundant nonhistone proteins found in all eukaryotic nuclei and are capable of binding/bending DNA. The human HMGB1 is composed of two binding motifs, known as Boxes A and B, are L-shaped alpha-helix structures, followed by a random-coil acidic tail that consists of 30 Asp and Glu residues. This work aimed at evaluating the role of the acidic tail of human HMGB1 in protein stability and DNA interactions. For this purpose, we cloned, expressed and purified HMGB1 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 64 publications
1
29
1
Order By: Relevance
“…In circularization assays the AB protein bent DNA more effectively than either of the single HMG box domains [18,19], and the full length protein at low concentrations [18]. In contrast to our findings, previous ensemble FRET experiments found that the AB protein bent DNA to a lesser extent than full length HMGB1 [24]. It is possible, however, that the DNA in these experiments was not fully occupied by the AB protein; therefore the measured FRET would be the average of the FRET from unbound DNA and bent DNA in the population, resulting in an apparent lower level of bending for the population.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In circularization assays the AB protein bent DNA more effectively than either of the single HMG box domains [18,19], and the full length protein at low concentrations [18]. In contrast to our findings, previous ensemble FRET experiments found that the AB protein bent DNA to a lesser extent than full length HMGB1 [24]. It is possible, however, that the DNA in these experiments was not fully occupied by the AB protein; therefore the measured FRET would be the average of the FRET from unbound DNA and bent DNA in the population, resulting in an apparent lower level of bending for the population.…”
Section: Discussioncontrasting
confidence: 97%
“…Dual-laser optical tweezer experiments showed that the linked A and B boxes of HMGB1 bend DNA to a somewhat lesser degree than a single HMG box [22], and similar results were obtained using atomic force microscopy [23]. Other studies have shown that deleting the acidic C-terminal tail from full length HMGB1 can enhance bending [18], while others reported that deleting the tail reduces bending [24]. Thus, the mechanism by which HMGB1 bends DNA, and the relative contributions of the A box, B box, and C-terminal tail to bending are not completely clear.…”
Section: Introductionmentioning
confidence: 71%
“…Another peptide in the B box (130-139) is responsible for promoting erythroleukemia cell differentiation, where the presence of extracellular HMGB1 is essential in erythroid differentiation 21. The C-terminal tail is responsible for DNA damage repair and DNA bending, which then promotes other transcription factors to bind DNA 22,23. The significance of this C-terminal tail lies on its role in increasing the structural stability of HMGB1 and binding to A and B box alternatively 24,25.…”
Section: Structure and Release Of Hmgb1mentioning
confidence: 99%
“…NABPs immobilized on PSMA/polystyrene microfiber meshes inhibited negatively charged polymeric molecules such as DNA, RNA and heparan sulfate [41], but did not inhibit Pam3CSK4, a cationic amphiphilic lipopeptide, and anionic metabolic products (e.g., ATP and uric acid). Furthermore, the NABP-immobilized microfiber meshes captured and removed circulating HMGB1, a DNA-binding protein composed of two positively charged DNA-binding motifs and a C-terminal acidic tail [42]. This highly negatively charged C-terminal domain likely binds to NABPs.…”
Section: Discussionmentioning
confidence: 99%